Some Relevant Aspects of the New Labor Procedural Law and Current Issues Interview with Dr. Luis Manuel Vinatea Recoba - Chumberiza Tupac Yupanqui, Mayté Pamela (2016)
The present interview makes a recount of some relevant aspects about the New Labour Procedural Law and his main contribution on resolution of labor conflicts. Also, gives the interviewed opinion about two relevant current events: the binding precedent Huatuco and the accomplishments of SUNAFIL, about one year of its lifespan.